The rise of Athens : the story of the world's greatest civilization - Everitt, Anthony (Random House, 2016)
"A magisterial account of how a tiny city-state in ancient Greece became history's most influential civilization, from the bestselling author of acclaimed biographies of Cicero, Augustus, and Hadrian"--